Site web locale pour la faculté des mathématiques et de l’informatique de l’université de M’sila - NOUASRI, Hamza (FACULTE DES MATHEMATIQUES ET DE L’INFORMATIQUE - UNIVERSITE MOHAMED BOUDIAF - M’SILA, 2016)
The goal of this project is the design and presentation of a local website for communication at the faculty MI University of Mohamed BoudiafM'sila, which can facilitatethe communication and the exchange of information between students, teachers and administration of faculty MI. For this application, we have chosen the UML modeling language that meets all our needs to this project, and for the implementation and realization, we have also chosen JetBrainsPhpStormas development environment with programming languages like Ajax, JQuery, JavaScript, CSS, HTML5, PHP.
Keywords: web locale,mathématiques et de l’informatique,faculté